Climate Change, Vulnerability, Social Conflicts and Human Displacement in the Andes: The case of Huaytapallana Glacier - Altamirano, Téofilo (2020)
The objective of this review was to identify the links between Climate Change, Vulnerability, Social Conflicts and Human Displacement in the Andes. The different factors that influence the vulnerability of people and communities are analyzed, such as the diversity of the impacts of climate change, the retreat of glaciers, the loss of biological diversity, health, agricultural production and scenarios with the presence of water scarcity. Adaptive behaviors are observed in the inhabitants of Andean communities, but they are not sufficient, because in many occasions people are forced to migrate to other cities. Five ways of responding to climate risks or hazards are suggested: 1) reduction and control of global warming, 2) adaptation to conditions resulting from climate change, 3) resistance, 4) mitigation, and 5) involuntary displacement. Finally, it concludes by stating that there is an intricate link between global warming, climate change, vulnerability and social conflicts, and that migration is a product of climate change.